Prevalence of depression, anxiety and stress among patients attending periodontal clinic - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (2017)
Objectives: The main objectives of our study are to assess the rate and severity of depression, anxiety and stress symptoms and to identify the possible association between these emotional disturbances with oral health problems. Methodology: This is a cross sectional study conducted on a sample of 159 patients with oral health problems including periodontitis and gingivitis attending the periodontal clinic, Kulliyyah of Dentistry, International Islamic University Malaysia. The prevalence and severity of depressive, anxiety and stress symptoms were assessed among those patients by using the self-rating Bahasa Malaysia version of the Depression Anxiety and Stress Scales (DASS-21). Results: The overall rate of depression, anxiety, and stress among patients was 18.9%, 36.5% and 19.5% respectively. Regarding the severity of the symptoms, it was found that 3.8%, 6.3 % and 2.5% of the patients had clinically significant depression, anxiety and stress respectively. Although patients with periodontitis had higher mean scores of depression, anxiety and stress than those with gingivitis but it was not statistically significant. Conclusion: Emotional disturbances in the form of depression, anxiety and stress are existing in high rates among patients with periodontal problem that require early detection and intervention.